Salen/salan metallic complexes as redox labels for electrochemical aptasensors. Issue 85 (9th October 2019) - Ben Jrad, Amani; Kanso, Hussein; Raviglione, Delphine; Noguer, Thierry; Inguimbert, Nicolas; Calas-Blanchard, Carole
Abstract : We provide a new route for the functionalization of electrode supporting aptamers conjugated to a salan chelator useful in biosensor devices. Abstract : This work presents the synthesis and characterization of salen/salan metal complexes for their future application as electrochemical labels in affinity sensors. Due to its stability and electrochemical properties, an oxovanadium salan complex was selected and coupled to an estradiol-specific aptamer. The response of the resulting aptasensor was shown to decrease with increasing estradiol concentration.